Systematic theology ; v. 3 - Hodge, Charles, 1797-1878 (Grand Rapids, MI Eerdmans, 1871)
Contents : v. 3 : pt 3(cont), Soteriology; pt 4, Eschatology. Includes bibliographical references.
1952 reprint
Keywords: Theology, doctrinal